The Role of Science in Handling Stunting in Selengen Village, Kayangan District - Taufik, M.; Hamdani, Muh; Azri, Saepul; Jati, Indra; Hadi, Samsul; Isnayadi, Raden (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The role of science is the main focus discussed in this paper. Knowledge is something that ordinary people must have, such as knowledge about how to care for children in terms of parenting, food, and things that must be paid attention to in terms of a child's health. The aim is so that parents understand how to deal with stunting through science. The reason we took this topic because we brought the theme from the STKIP Hamzar campus with the theme